O-Alkylation versus C-Alkylation in the Synthesis of 5,6-Dihydro-4H-oxacin-4-ones: Theoretical Approach - Rosas, Noe; Salcedo, Roberto; Sharma, Pankaj; Luis Arias, Jose; Arellano, Ivonne; Cabrera, Armando (Asian Journal of Chemistry, 2010)
The condensation of α-ketoalkynes with p-nitrobenzaldehyde, in the presence of lithium diisopropyl amide (LDA) used as a strong base, results exclusively in the O-alkylation product i.e., the 5,7-dialkyl-6-(4-nitro-phenyl)-2-phenyl-8- phenylethynyl-5,6-dihydro-oxacin-4-ones. No C-alkylation product was found. The energy calculation of the two possible transition states shows a preferentially low activation energy for the 8-endo-dig cyclization pathway.